Sulfonylurea Herbicide-Resistant Study on Broadleaf Weeds in The Lowland Rice Production Center in West Java, Indonesia - Evar, Fitrawaty Orista; Guntoro, Dwi; Chozin, M. A.; Irianto, M. Yuli (Department of Agronomy and Horticulture, IPB University, 2022)
Most rice growers in Indonesia use herbicides for weed control. However, intensive use of herbicides can lead to the weeds to become resistant to the chemicals. The objective of this study was to determine the resistance status of weeds Ludwigia octovalvis, Sphenoclea zeylanica, Monochoria vaginalis in lowland rice in West Java, Indonesia. The study was started by planting three species of weeds, L. octovalvis, S. zeylanica, M. vaginalis, which were then treated with metsulfuron-methyl and penoxsulam herbicides. The study was conducted from January to May 2020 at Cikabayan Experimental Greenhouse, IPB University. The experiment was arranged in a randomized complete block design with four replications. The first factor was the origin of weeds, exposed weeds (Karawang and Subang), and not exposed to herbicides (Bogor); the second factor was the rates of the herbicide, i.e., 0, 2.5, 5, 10, 20, 40, 80 and 160 g. ha-1 for metsulfuron- methyl, and 0, 50, 100, 200, 400, 800, 1600, and 3200 ml.ha-1 for penoxsulam. The results showed that based on the resistance ratio, S. zeylanica and M. vaginalis from Karawang and Subang, and L. octovalvis from Subang, indicated a low resistance to metsulfuron-methyl, L. octovalvis from Karawang was still sensitive to metsulfuron-methyl. L. octovalvis, S. zeylanica, and M. vaginalis from Karawang and Subang were still sensitive to penoxsulam herbicides. This information would be useful to develop a strategy of weed management for important food crops.